2016
DOI: 10.1088/0256-307x/33/11/116102
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Thermophysical Properties for Quinary High-Entropy NiFeCoCrCu/Al Alloys

Abstract: Two quinary high-entropy alloys (HEAs) with equiatomic concentrations formed by doping either Cu or Al elements into the quaternary NiFeCoCr alloy are produced by arc melting and spray casting techniques. Their entropy of fusion, thermal expansion coefficient and thermal diffusivity are experimentally investigated with differential scanning calorimetry, dilatometry and laser flash methods. The NiFeCoCrCu HEAs contain a face-centered cubic high-entropy phase plus a minor interdendritic (Cu) phase and display a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The theoretical density of a solid-solution alloy can be roughly estimated from the atomic fraction, atomic weight and density of each constituent element [52]. A recent experimental study of thermophysical properties has shown that the theoretical density and experimental value of a NiFeCoCrCu alloy were 8.324 and 8.295 g cm −3 [17], respectively. The value of 8.356 g cm −3 used in the simulation is the default value in SRIM.…”
Section: Ni Ion Irradiationmentioning
confidence: 99%
See 2 more Smart Citations
“…The theoretical density of a solid-solution alloy can be roughly estimated from the atomic fraction, atomic weight and density of each constituent element [52]. A recent experimental study of thermophysical properties has shown that the theoretical density and experimental value of a NiFeCoCrCu alloy were 8.324 and 8.295 g cm −3 [17], respectively. The value of 8.356 g cm −3 used in the simulation is the default value in SRIM.…”
Section: Ni Ion Irradiationmentioning
confidence: 99%
“…These results indicate that, after the initial thermodynamic equilibrium is reached (∼300 s), the microstructure is driven towards a new stable state during the extended annealing to 1942 s. The melting temperature of NiFeCoCrCu HEA films can be estimated by averaging the solidus temperature and liquidus temperature of the material [90] or using the rule of mixture (ΣX i • T i m ) where X i and T i m are the molar fraction and melting temperature of the constituent element i, respectively [91]. In recent work [17], a Ni-Fe-Co-Cr-Cu fcc HEA was produced with a matrix phase formed by approximately 22 at% of Ni, Fe, Co, and Cr plus a reduced amount of ∼11% Cu together with an embedded Cu-enriched (∼67%) solid solution phase. The liquidus temperature of this alloy was determined to be 1382 °C (1655 K).…”
Section: Thermally-induced Growth Of Nanocrystalline Nifecocrcu Thin ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, ceramic materials have low thermal expansion coefficients but their conductivities are usually poor. Recent investigations suggest that negative thermal expansion materials could be used to prepare low thermal expansion materials by partial ion substitution, doping, or compounding with positive thermal expansion materials, [1][2][3] which could also result in high conductivity. [4][5][6][7][8] ZrV 2 O 7 is one of the isotropic negative thermal expansion materials but its negative thermal expansion is only present after a phase transition.…”
Section: Introductionmentioning
confidence: 99%